Edmund G. Ross : Soldier, Senator, Abolitionist - Ruddy, Richard A., 1939- (Book collections on Project MUSE., 2013)
"Ross was a significant abolitionist, journalist, Union officer, and, eventually, territorial governor of New Mexico. This first full-scale biography of Ross reveals his importance in the history of the United States"--Provided by publisher